Efek Model Pembelajaran Scientific Inquiry terhadap Keterampilan Proses Sains (KPS) Siswa - Sri Handayani Parinduri; Fitriani Harahap (Institut Agama Islam Negeri Padangsidimpuan, 2023)
This study aims to analyze the influence of the scientific inquiry learning model on students' science process skills on temperature and heat material. This research is a quasi-experimental research. The population of this study is all students of class XI IPA SMA Private Campus Padangsidimpuan T.P. 2022/2023. The sample consists of two classes obtained using the cluster random sampling technique. The experimental class is taught with the scientific inquiry learning model and the second class is taught with conventional learning. The research instrument is a test of science process skills complemented by observation. The data in this study were analyzed using an independent sample t-test. The results showed that the science process skills of students taught using the scientific inquiry learning model were better than conventional learning.